(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This research paper explores the intricate relationship between food, nutrition, and economics, unveiling the potential of economic strategies to enhance public health outcomes. Through a synthesis of case studies, behavioural insights, and cost-benefit analyses, we investigate the efficacy of nutritional interventions in addressing health challenges while yielding economic benefits. The paper delves into diverse dimensions, including school feeding programs, nutritional education initiatives, food subsidies, and behavioural nudges. By analysingcase study scenarios and employing rigorous economic methodologies, we showcase the multifaceted impact of nutrition on individual well-being and societal progress. The findings underscore the significance of evidence-based strategies in designing effective nutritional policies that contribute to both health improvement and economic growth. This study highlights the symbiotic relationship between nutrition and economics, advocating for holistic approaches to public health and economic development.